Analysis of plant hormone profiles in response to moderate dehydration stress. (20th February 2017) - Urano, Kaoru; Maruyama, Kyonoshin; Jikumaru, Yusuke; Kamiya, Yuji; Yamaguchi‐Shinozaki, Kazuko; Shinozaki, Kazuo
Summary: Plant responses to dehydration stress are mediated by highly complex molecular systems involving hormone signaling and metabolism, particularly the major stress hormone abscisic acid (ABA) and ABA‐dependent gene expression. To understand the roles of plant hormones and their interactions during dehydration, we analyzed the plant hormone profiles with respect to dehydration responses in Arabidopsis thaliana wild‐type (WT) plants and ABA biosynthesis mutants ( nced3‐2 ). We developed a procedure for moderate dehydration stress, and then investigated temporal changes in the profiles of ABA, jasmonic acid isoleucine (JA‐Ile), salicylic acid (SA), cytokinin (trans‐zeatin, tZ), auxin (indole‐acetic acid, IAA), and gibberellin (GA4 ), along with temporal changes in the expression of key genes involved in hormone biosynthesis. ABA levels increased in a bi‐phasic pattern (at the early and late phases) in response to moderate dehydration stress. JA‐Ile levels increased slightly in WT plants and strongly increased in nced3‐2 mutant plants at 72 h after the onset of dehydration. The expression profiles of dehydration‐inducible genes displayed temporal responses in an ABA‐dependent manner. The early phase of ABA accumulation correlated with the expression of touch‐inducible genes and was independent of factors involved in the major ABA regulatory pathway, including the ABA‐responsive element‐binding (AREB/ABF) transcription factor. JA‐Ile, SA, and tZ were negatively regulated during the late dehydration response phase. Transcriptome analysis revealed important roles for hormone‐related genes in metabolism and signaling during dehydration‐induced plant responses. Significance Statement: Plant growth and crop production are severely affected by dehydration stress. Characterization of plant hormone metabolism and signalling is needed to precisely clarify the regulatory networks that operate under dehydration stress. Here we developed a procedure for simulating moderate dehydration stress, and then investigated temporal changes in hormone profiles and the expression of key hormone biosynthetic genes in Arabidopsis thaliana wild‐type plants and ABA biosynthesis mutants.